Ontology Development For Supporting The Decision On Selecting An Individual Educational Trajectory; Advances in Computer Science Research; Vol. 72 : Information technologies in Science, Management, Social sphere and Medicine (ITSMSSM 2017) - Zakharova A. A. Aleksandra Aleksandrovna (2017, 2017)
Title screen